Mitochondrial signaling contributes to disuse muscle atrophy - Powers, Scott K. (American Physiological Society, 2012)
It is well established that long durations of bed rest, limb immobilization, or reduced activity in respiratory muscles during mechanical ventilation results in skeletal muscle atrophy in humans and other animals. The idea that mitochondrial damage/dysfunction contributes to disuse muscle atrophy originated over 40 years ago. These early studies were largely descriptive and did not provide unequivocal evidence that mitochondria play a primary role in disuse muscle atrophy. However, recent experiments have provided direct evidence connecting mitochondrial dysfunction to muscle atrophy. Numerous studies have described changes in mitochondria shape, number, and function in skeletal muscles exposed to prolonged periods of inactivity. Furthermore, recent evidence indicates that increased mitochondrial ROS production plays a key signaling role in both immobilization-induced limb muscle atrophy and diaphragmatic atrophy occurring during prolonged mechanical ventilation. Moreover, new evidence reveals that, during denervation-induced muscle atrophy, increased mitochondrial fragmentation due to fission is a required signaling event that activates the AMPK-FoxO3 signaling axis, which induces the expression of atrophy genes, protein breakdown, and ultimately muscle atrophy. Collectively, these findings highlight the importance of future research to better understand the mitochondrial signaling mechanisms that contribute to disuse muscle atrophy and to develop novel therapeutic interventions for prevention of inactivity-induced skeletal muscle atrophy.